Genetic Architecture and Candidate Genes for Deep-Sowing Tolerance in Rice Revealed by Non-syn GWAS - Zhao, Yan; Zhao, Weipeng; Jiang, Conghui; Wang, Xiaoning; Xiong, Huaiyang; Todorovska, Elena G.; Yin, Zhigang; Chen, Yanfa; Wang, Xin; Xie, Jianyin; Pan, Yinghua; Rashid, Muhammad A. R.; et al. (Frontiers in Plant Science, 2018)
Dry direct-seeding of rice is rapidly increasing in China, but variable planting depth associated with machine sowing can lead to low seedling emergence rates. Phenotype analysis of 621 rice accessions showed that mesocotyl length (ML) was induced by deep soil covering and was important in deep-sowing tolerance in the field. Here, we performed and compared GWAS using three types of SNPs (non-synonymous SNP, non-synonymous SNPs and SNPs within promoters and 3 million randomly selected SNPs from the entire set of SNPs) and found that Non-Syn GWAS (GWAS using non-synonyomous SNP) decreased computation time and eliminated confounding by other loci relative to GWAS using randomly selected SNPs. Thirteen QTLs were finally detected, and two new major-effect genes, named OsML1 and OsML2, were identified by an integrated analysis. There were 2 and 7 non-synonymous SNPs in OsML1 and OsML2, respectively, from which 3 and 4 haplotypes were detected in cultivated rice. Combinations of superior haplotypes of OsML1 and OsML2 increased ML by up to 4 cm, representing high emergence rate (85%) in the field with 10 cm of soil cover. The studies provide key loci and naturally occurring alleles of ML that can be used in improving tolerance to dry direct-seeding.